Digital materials design by thermal-fluid science for multi-metal additive manufacturing. (15th May 2021) - Shinjo, Junji; Panwisawas, Chinnapat
Abstract: Metal additive manufacturing is promising for designing advanced metallic parts of complex geometries. The challenge lies in process control on melt flow dynamics, alloy mixing and vapour mass loss, which is significantly vital for the final quality. A high-fidelity thermal-solutal-fluid modelling approach including accurate tracking of surface shape, thermo-capillary dynamics and vaporisation has been developed. Multi-species formulations are also included for multi-metal simulation. Using this method, the physical link between metal vapour mass loss and melt flow process for 21 transition metals and 3 binary alloys is investigated. The mass loss rate is governed by a fluid dynamic parameter of Reynolds number with a simple proportional correlation linked with thermal-fluid behavior of the melt pool, and convective mixing further complicates the behaviour in in-situ binary alloying. The digital materials approach is effective in understanding complex interdependent thermal-fluid flow dynamics and can advance process-based materials design. Graphical abstract: Image, graphical abstract